2016
DOI: 10.5109/1657381
|View full text |Cite
|
Sign up to set email alerts
|

Desiccant Air-Conditioning System for Storage of Fruits and Vegetables : Pakistan Preview

Abstract: In the present study the desiccant airconditioning system has been investigated for the on-farm storage of fruits and vegetables in Pakistan. In this regard, ideal storage zone for the studied agricultural products is established in order to ascertain the system applicability. The dehumidification performance of the silica-gel based desiccant wheel has been analysed with low regeneration temperature (50°C) by using the model of Beccali et. al. Three environmental conditions (A: highly humid, B: moderately humi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Therefore, it has been used for dehumidification and air-conditioning processes for various agricultural applications e.g. greenhouses [3] and agricultural product storage [4] . Certainly, desiccants possess the drying potential that can be used for various agricultural products, and consequently many studies have been reported in the literature [1,[5][6][7] .…”
Section: Introduction mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it has been used for dehumidification and air-conditioning processes for various agricultural applications e.g. greenhouses [3] and agricultural product storage [4] . Certainly, desiccants possess the drying potential that can be used for various agricultural products, and consequently many studies have been reported in the literature [1,[5][6][7] .…”
Section: Introduction mentioning
confidence: 99%
“…Post-harvested agricultural products including wheat grains possess high moisture level at the time of harvest and therefore cannot be stored for a long time unless proper storage/treatment has been employed [4] . In this regard, wheat grains need to dry up to a level of 14% moisture content (dry basis) to avoid mold growth as well as the insect's attack [34,35] .…”
Section: Introduction mentioning
confidence: 99%
“…It is mainly due to food wasting, improper management, and high cost of food storage and transportation. Food storage is usually expensive and complicated due to the involvement of numerous physiochemical and biological processes, for example, respiration, transpiration, fermentation, and so on [7]. Moreover, storage conditions and nature of storage are completely different for different types of food, which may be categorized as follows:…”
Section: Food Storage and Transportationmentioning
confidence: 99%
“…For example, cooling and humidification is required in summer season of Multan (Pakistan), whereas heating and humidification is required in dry winters of Fukuoka (Japan) [3]. Certainly, there could be numerous AC applications which may require specific conditions of T a and RH, for example, animals' AC [4], greenhouse AC [2,5], agricultural products' storage and preservation [6,7], and so on. The requirements of T a and RH vary dynamically with respect to time and may even vary from species to species [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation